Protein and Mineral Contents of Cocoa Beans Fermentation from Luwu Timur Regency, South Sulawesi - Asma Assa; Alfian Noor; Misnawi Misnawi; Muh. Natsir Djide; Muliadi Muliadi (Indonesian Coffee and Cocoa Research Institute, 2017)
Cocoa beans are raw materials of cocoa processed food products rich in protein and minerals. Availability of sufficient quantities greatly determines the nutritional quality of the food. One of the post-harvest processes affecting the protein and minerals contents in cocoa beans is fermentation. The purpose of this study was to determine the protein, macro, and micronutrients contents in fermented cocoa beans of PBC 123, BR 25, and MCC 02 clones with fermentation time variations for 24, 48, 72, 96, and 120 hours. Methods of analysis used Kjeldahl and Atomic Absorption Spectrophotometer. The results showed that clones, fermentation time, and their interaction affect protein, macro and micronutrients content in cocoa beans. The interaction between BR 25 clone and 48-hour fermentation time showed the highest protein content (13.34%). The highest macronutrients content were found in PBC 123 clone with 72-hour fermentation time for Ca, in MCC 02 clone with 24-hour fermentation time for Mg, in BR 25 clone with 72-hour fermentation time for Na, and in BR 25 clone with 24-hour fermentation time for K. The highest micronutrients contents were found in PBC 123 clone with 96-hour fermentation time for Fe, in MCC 02 clone with 120-hour fermentationtime for Mn, and in BR 25 clone with 96-hour fermentation time for Zn. Variations of protein, macronutrients and micronutrients contents in cocoa beans were affected by clone variety and fermentation time treatment.